Integrated Management using Plant Extracts and Bacillus subtilis for Botrytis cinerea Causing Gray Mold Disease of Bell Pepper - Mahmood, Basharat; Tariq, Maryam; Ahmad, Imtiaz; Zafar, Lubna; Zafar, Tehmina; Saleem, Muhammad; Rasheed, Mansoor; Kakar, Bismillah Khan; Nadeem, Muhammad; Mahmood, Laiba; Mushtaq, Saqlain (Journal of Agriculture and Veterinary Science, 2024)
Botrytis cinerea, the gray mold pathogen, is a major threat to bell pepper production, causing huge losses in yield. This research examines the effectiveness of plant extracts and the biocontrol product Bacillus subtilis in controlling gray mold disease on bell peppers. Fruits of bell pepper showing symptoms of gray mold were studied, and was identified on the basis of morphological analysis. Antifungal activity of neem (Azadirachta indica), garlic (Allium sativum), and thyme (Thymus vulgaris) extracts alone and in combination with B. subtilis was determined in vitro. Greenhouse experiments determined the incidence and severity of disease caused by B. cinerea under different treatment regimes. In vitro tests indicated that B. subtilis had the highest antifungal activity with 60% inhibition of B. cinerea growth, while the plant extracts exhibited moderate to high activity. When all three plant extracts were combined with B. subtilis, 80% growth inhibition of the fungus was achieved, which revealed a significant synergistic effect. In greenhouse experiments, combined treatment with neem, garlic, thyme, and B. subtilis reduced both disease incidence and severity significantly in comparison to individual treatments and control. The combination of neem, garlic, and thyme extracts with B. subtilis is a very effective method for managing Botrytis cinerea in bell pepper crops. This method not only minimizes the use of synthetic fungicides but also supports sustainable agriculture. The research identifies the possibility of utilizing natural and biocontrol agents in the management of gray mold disease as a promising alternative for crop protection.
Keywords: Botrytis cinerea; B. subtilis; Gray mold; Neem; Garlic; Thyme